Carbon nanotubes overgrown and ingrown with nanocrystalline diamond deposited by different CVD plasma systems. Issue 12 (28th August 2014) - Varga, M.; Vretenar, V.; Izak, T.; Skakalova, V.; Kromka, A.
<x xml:space="preserve">Abstract</x> In this work we investigate the growth of diamond film on a porous single‐wall carbon nanotubes (SWNT) paper by employing three different Chemical Vapour Deposition (CVD) systems: plasma‐assisted hot filament, focused microwave plasma and linear antenna microwave plasma. We observe that the diamond growth is strongly affected by the different conditions in each of the CVD processes resulting in different SWNT/diamond composite structures. It is also found that only the linear antenna microwave plasma CVD process allows penetration of the activated growth species into the volume of the SWNT paper, whereas using the other methods, the diamond grains are formed on the SWNT paper surface only. Moreover, the growth of diamond structures within the substrate volume is strongly influenced by the CH4/CO2/H2 gas content ratio. A key factor influencing the formation of a compact SWNT/diamond composite is keeping the equilibrium between two competitive processes: establishing conditions where the diamond structure can grow while etching/damage of the SWNT paper is still kept at a minimum. The morphology and chemical composition of formed composite materials were characterized by scanning electron microscopy and Raman spectroscopy.